L’effet de la pandémie de la COVID-19 sur Résonances et ses artistes - Deschamps, Marjorie; Azoulay, Yaëlle; Azoulay, Noémie (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Marjorie Deschamps, Yaëlle Azoulay, and Noémie Azoulay, co-founders of the independent booking agency Résonances, describe the challenge of supporting their artists while simultaneously pivoting their business model and negotiating their own work-life balances. They describe a new digital capture and broadcasting project, La Trame, that will offer alternative modes of diffusion for their artists and more socially engaged, community-based programming.